2010
DOI: 10.1128/jb.00003-10
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of the E Loop, a Novel Motif Conserved in the Lantibiotic Immunity ATP-Binding Cassette Transport Systems

Abstract: Lantibiotics are peptide-derived antibacterial substances produced by some Gram-positive bacteria and characterized by the presence of unusual amino acids, like lanthionines and dehydrated amino acids. Because lantibiotic producers may be attacked by self-produced lantibiotics, they express immunity proteins on the cytoplasmic membrane. An ATP-binding cassette (ABC) transport system mediated by the LanFEG protein complex is a major system in lantibiotic immunity. Multiple-sequence alignment analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…While penB is responsible for dehydration of serine and threonine residues, the cyclase (penC) catalyzes the nucleophilic attack of a cysteine on the dehydrated residues. A dedicated lantibiotic ABC transporter gene (penT), which is required for the export of penisin, was also encoded with highly conserved domains such as Walker A (401-GRNGSGKTT-409), Q-loop (445-VVFQDFV-452), signature sequence (510-SGGQW QR-517), Walker B (529-LYVLDE-535), and H-loop (564-SHR-567), as described in the literature (36). Further, the genome also harbors an additional lantibiotic dehydratase gene similar to penD, which is unusual for the penisin gene cluster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While penB is responsible for dehydration of serine and threonine residues, the cyclase (penC) catalyzes the nucleophilic attack of a cysteine on the dehydrated residues. A dedicated lantibiotic ABC transporter gene (penT), which is required for the export of penisin, was also encoded with highly conserved domains such as Walker A (401-GRNGSGKTT-409), Q-loop (445-VVFQDFV-452), signature sequence (510-SGGQW QR-517), Walker B (529-LYVLDE-535), and H-loop (564-SHR-567), as described in the literature (36). Further, the genome also harbors an additional lantibiotic dehydratase gene similar to penD, which is unusual for the penisin gene cluster.…”
Section: Resultsmentioning
confidence: 99%
“…In our annotation and analysis, we found a penC gene with 92% similarity to the LanC-like protein of P. elgii B69 with all conserved domains. Unlike paenicidin A, the ABC transporter present in the biosynthetic cluster of penisin is presumed to be involved in both transportation and immunity, as observed for other lantibiotics (36). To confirm the formation of the thioether bond between cysteine amino acids present in penisin, we performed PEGylation experiments with native and reduced forms of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…SmbT encodes permease component and is 238 residues long with six transmembrane domains. SmbF, on the other hand, encodes a 274 residues long protein with ATPase signature sequences (52). The promoter for smb locus lies ϳ3.0 kb upstream of the smbFT genes.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies suggest that, unlike general ABC transporters that transport substrates across the membranes, the ABC transporters related to immunity function transport specific lantibiotics from the membrane to the extracellular space (28,29,55). A recent study identified the presence of a conserved motif, termed the E-loop, in the ABC transporters belonging to LanFEG and BcrAB families (52). This E-loop structure plays an important role in the function of these transporters and perhaps induces structural changes in the transmembrane domains.…”
Section: Discussionmentioning
confidence: 99%
“…In at least some lantibiotic transporters, the E-loop is necessary for immunity toward the produced compound. In NukF of Staphylococcus warneri ISK-1, E85Q and E85A substitutions in the E loop impaired immunity to nukacin ISK-1, while ATPase activity remained at wild-type (WT) levels (46). Both PspT and PspZ contain a Q-loop, while PspF contains an E-loop.…”
Section: Identification Of P Alba As a Planosporicin Producer Fourmentioning
confidence: 99%